It's not an "Unpredictable Solution" Problem!

Algebra Level 4

{ 2 x + y + x y = 2 y + 3 z + y z = 7 2 x + 3 z + x z = 30 \begin{cases} 2x+y+xy = 2 \\ y+ 3z + yz = 7 \\ 2x + 3z + xz = 30 \end{cases}

Given that x , y , x, \space y, and z z are all integers that satisfy the system of equation above. Find the positive value of x 3 + 10 y 3 + z 3 4 \sqrt[4]{x^{3} + 10y^{3} + z^{3}} .


Try another problem on my set! Let's Practice


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

{ 2 x + y + x y = 2 y + 3 z + y z = 7 2 x + 3 z + x z = 30 \begin{cases} 2x+y+xy = 2 \\ y+ 3z + yz = 7 \\ 2x + 3z + xz = 30 \end{cases}


The first equation, 2 x + y + x y = 2 y + x y = 2 2 x y ( x + 1 ) = 2 2 x y = 2 2 x x + 1 \begin{aligned} 2x + y + xy & = 2 \\ y + xy & = 2-2x \\ y(x+1) & = 2- 2x \\ y & = \dfrac{2-2x}{x+1} \end{aligned}


The third equation, 2 x + 3 z + x z = 30 x z + 3 z = 30 2 x z ( x + 3 ) = 30 2 x z = 30 2 x x + 3 \begin{aligned} 2x + 3z + xz & = 30 \\ xz + 3z & = 30-2x \\ z(x+3) & = 30-2x \\ z & = \dfrac{30-2x}{x+3} \end{aligned}


The second equation, y + 3 z + y z = 7 y + 3 z + y z + 3 = 10 ( y + 3 ) ( z + 1 ) = 10 ( 2 2 x x + 1 + 3 ) ( 30 2 x x + 3 + 1 ) = 10 ( 2 2 x + 3 x + 3 x + 1 ) ( 30 2 x + x + 3 x + 3 ) = 10 ( x + 5 x + 1 ) ( 33 x x + 3 ) = 10 28 x x 2 + 165 = 10 ( x 2 + 4 x + 3 ) 28 x x 2 + 165 = 10 x 2 + 40 x + 30 11 x 2 + 12 x 135 = 0 ( 11 x + 45 ) ( x 3 ) = 0 \begin{aligned} y + 3z + yz & = 7 \\ y + 3z + yz + 3 & = 10 \\ (y+3)(z+1) & = 10 \\ \left( \color{#D61F06} \dfrac{2-2x}{x+1} \color{#333333} + 3 \right)\left( \color{#3D99F6} \dfrac{30-2x}{x+3} \color{#333333} + 1 \right) & = 10 \\ \left( \color{#D61F06} \dfrac{2-2x+3x+3}{x+1} \color{#333333} \right)\left( \color{#3D99F6} \dfrac{30-2x + x+3}{x+3} \color{#333333} \right) & = 10 \\ \left( \dfrac{ \color{#E81990} x+5}{\color{#20A900} x+1} \color{#333333} \right)\left( \dfrac{\color{#E81990} 33-x}{\color{#20A900} x+3} \color{#333333} \right) & = 10 \\ \color{#E81990} 28x - x^{2} + 165 & \color{#333333} = 10( \color{#20A900} x^{2} + 4x + 3) \\ 28x - x^{2} + 165 & = 10x^{2} + 40x +30 \\ 11x^{2} + 12x -135 & = 0 \\ (11x+45)(x-3) & = 0 \end{aligned}


After all, we have x = 3 x= 3 ; Since x is an integer \Rightarrow \color{#EC7300} \text{ Since } \space x \space \text{ is an integer}

Substituting, we have y = 1 y = -1 and z = 4 z= 4 .

Now, we have x 3 + 10 y 3 + z 3 4 = 3 3 + 10 ( 1 ) 3 + 4 3 4 = 81 4 = ± 3 \sqrt[4]{x^{3} + 10y^{3} + z^{3}} = \sqrt[4]{3^{3} + 10(-1)^{3} + 4^{3}} = \sqrt[4]{81} = \pm 3 .

The positive value of x 3 + 10 y 3 + z 3 4 \sqrt[4]{x^{3} + 10y^{3} + z^{3}} is 3 \boxed{3} .

Relevant wiki: Quadratic Diophantine Equations - Solve by Simon's Favorite Factoring Trick

{ 2 x + y + x y = 2 ( x + 1 ) ( y + 2 ) = 4 . . . ( 1 ) y + 3 z + y z = 7 ( y + 3 ) ( z + 1 ) = 10 . . . ( 2 ) 2 x + 3 z + x z = 30 ( x + 3 ) ( z + 2 ) = 36 . . . ( 3 ) \begin{cases} 2x+y+xy = 2 & \implies (x+1)(y+2) = 4 & ...(1) \\ y+3z+yz = 7 &\implies (y+3)(z+1) = 10 & ...(2) \\ 2x+3z+xz = 30 & \implies (x+3)(z+2) = 36 & ...(3) \end{cases}

From ( 1 ) : y + 2 = 4 x + 1 (1): \implies y + 2 = \dfrac 4{x+1} . From ( 3 ) : z + 2 = 36 x + 3 (3): \implies z+2 = \dfrac {36}{x+3} . Then, from ( 2 ) (2) :

( y + 3 ) ( z + 1 ) = 10 ( 4 x + 1 + 1 ) ( 36 x + 3 1 ) = 10 ( 4 + x + 1 ) ( 36 x 3 ) = 10 ( x + 1 ) ( x + 3 ) ( x + 5 ) ( 33 x ) = 10 ( x 2 + 4 x + 3 ) x 2 + 28 x + 165 = 10 x 2 + 40 x + 30 11 x 2 + 12 x 135 = 0 ( 11 x + 45 ) ( x 3 ) = 0 x = 3 x is an integer. \begin{aligned} (y+3)(z+1) & = 10 \\ \left(\frac 4{x+1} + 1\right) \left(\frac {36}{x+3}-1\right) & = 10 \\ (4+x+1)(36-x-3) & = 10(x+1)(x+3) \\ (x+5)(33-x) & = 10(x^2+4x+3) \\ -x^2 + 28x + 165 & = 10x^2 + 40x + 30 \\ 11x^2 + 12x - 135 & = 0 \\ (11x+45)(x-3) & = 0 \\ \implies x & = 3 & \small \color{#3D99F6} x \text{ is an integer.} \end{aligned}

When x = 3 x=3 , ( 1 ) : y + 2 = 4 x + 1 y = 1 (1): y + 2 = \dfrac 4{x+1} \implies y = -1 , ( 3 ) : z + 2 = 36 x + 3 z = 4 (3): z+2 = \dfrac {36}{x+3} \implies z = 4 .

x 3 + 10 y 3 + z 3 4 = 27 10 + 64 4 = 81 4 = 3 \implies \sqrt[4]{x^3+10y^3+z^3} = \sqrt[4]{27-10+64} = \sqrt[4]{81} = \boxed{3}

Similar to my solution! Nice work!

Fidel Simanjuntak - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...